ANALISIS JAWABAN TUGAS MAHASISWA PADA TUTORIAL ONLINE BERDASARKAN BLOOMS TAXONOMY - Sandra Sukmaning Adji (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2014)
The Open University (UT) provided by the educational staff of the Open University (UT) to help students overcome their learning difficulties. This paper focuses on the ability of students in doing the tasks, assigned by the tutor during the online tutorial activities. The study was conducted at the UT course tutorial activities of Environmental Chemistry Subject at the trial period of 2010.2, 2011.1 2011.2, 2012.1 and 2012.2 involving 81students. Data was obtained based on students answers to the assignments/tasks given by the tutor. The indicators used for analysis of students task answer were the students ability in Blooms taxonomy analyzing. The data then was analyzed into qualitative descriptive. Results showed: 1) All students were able to answer well for the ability of memory understanding and comprehension 2). Not all students were capable to reach higher level thinking i.e. analyzing and evaluating in answering the questions given. 3) Students gave positive respon in online tutorial activities and using the "open educational resources". Universitas Terbuka (UT) yang disediakan oleh staf pendidikan dari Universitas Terbuka (UT) untuk membantu siswa mengatasi kesulitan belajar mereka. Makalah ini berfokus pada kemampuan siswa dalam melakukan tugas, yang diberikan oleh guru selama kegiatan tutorial online. Penelitian dilakukan di UT kegiatan program tutorial Kimia Lingkungan Subjek pada masa percobaan 2010.2, 2.011,1 2.011,2, 2.012,1 dan 2.012,2 melibatkan 81 siswa. Data diperoleh berdasarkan jawaban siswa terhadap tugas / tugas yang diberikan oleh tutor. Indikator yang digunakan untuk analisis siswa jawaban tugas yang siswa kemampuan dalam taksonomi Bloom menganalisis. Data kemudian dianalisis menjadi deskriptif kualitatif. Hasil penelitian menunjukkan: 1) Semua siswa mampu menjawab dengan baik untuk kemampuan pemahaman memori dan pemahaman 2). Tidak semua siswa mampu mencapai yang lebih tinggi berpikir tingkat yaitu menganalisis dan mengevaluasi dalam menjawab pertanyaan-pertanyaan yang diberikan. 3) Siswa memberikan respon positif dalam kegiatan tutorial online dan menggunakan "sumber daya terbuka pendidikan".